Twelve Good Musicians: From John Bull to Henry Purcell - Bridge, Frederick, 1844-1924 (Salt Lake City, UT : Project Gutenberg, 2012)
"Twelve Good Musicians: From John Bull to Henry Purcell" by Sir Frederick Bridge is a historical account written in the early 20th century. The book delves into the lives and contributions of twelve significant English musicians spanning the 17th century, with musicianship from John Bull to Henry Purcell framing the history of English music in that period. It aims to illuminate their achievements and importance in a time often overlooked in musical discourse. At the start of this work, the author provides context about the relatively ignored 17th century in English music, referencing Sir Hubert Parry's assessment of the period as a blank slate musically. Bridge subsequently outlines his intention to combat this narrative by focusing on twelve notable composers, beginning with Dr. John Bull. He highlights Bull's pivotal role in music as the first Gresham Professor of Music and his diverse contributions to the musical landscape, from organ performance to potential authorship of England's national anthem. The opening effectively sets the stage for a deeper exploration of the selected musicians' lives and their lasting influences on English music history. (This is an automatically generated summary.)
Dr. John Bull, 1563(?)-1628 -- William Byrd, 1542-3-1623 -- Thomas Morley, 1557-1603 -- Thomas Weelkes, 1575(?)-1623 -- Orlando Gibbons, 1583-1625 -- Richard Deering, 1580(?)-1630 -- John Milton, 1553-1646-7 -- Henry Lawes, 1595-1662 -- Matthew Locke, 1630(?)-1677 -- Pelham Humfrey, 1647-1674 -- Dr John Blow, 1648-1708 -- Henry Purcell, 1658-1695.
Release date is 2012-06-07
Produced by Al Haines
Keywords: Musicians -- England